Peran Pendidik Agama Kristen Dalam Membangun Kesadaran Ekologis Berdasarkan Kajian Teks Kejadian 1: 26-28 - Silalahi, Edu Arto (JURNAL LUXNOS, 2025)
This study explores the role of Christian Religious Education in building awareness of the ecological crisis. The purpose of the study is to identify the contribution of teachers or educators in forming ecological awareness in Christian educational environments. The method used in compiling this article is a qualitative research method with literature studies. Through in-depth theological research, this study provides a comprehensive picture of the role of Christian religious education in instilling and building ecological awareness for students. The results of the study indicate that the awareness that God is the creator, God who blesses and gives mandates is an important theological foundation to understand in relation to ecological awareness. That both educators and students must have the same awareness of the reality of environmental damage in various places. Thus, this study confirms that Christian Religious Education has a significant role in helping students not only in relation to spiritual problems but also in understanding ecology so that they are prepared to become environmental conservation actors and act as agents of change for the continuation of the preservation of nature and all its contents.